The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1080/16070658.2016.1198618
|View full text |Cite
|
Sign up to set email alerts
|

Agreement between measured height, and height predicted from ulna length, in adult patients in Bloemfontein, South Africa

Abstract: Objective: To assess the agreement between measured height, and height predicted from ulna length using the Malnutrition Universal Screening Tool (MUST) equations, in adult patients admitted to government hospitals in Bloemfontein, South Africa. Design: Descriptive cross-sectional survey. Setting: Medical, surgical, pulmonary, orthopaedic, cardiovascular and general wards at Pelonomi, Universitas and National Hospitals in Bloemfontein. Subjects: All patients between 19 and 60 years, admitted during a two-week … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 29 publications
1
5
0
Order By: Relevance
“…On the other hand, published arm-based equations did not accurately predict height in a sample of 900 younger adults in KwaZulu-Natal, and the study concluded that sex-and racespecific equations are needed. 15 This concurs with the findings of van den Berg et al 1 that the ulna-based MUST equations overestimated height and predicted height that differed statistically significantly from stadiometer height in adult (20-60 years old) patients in a public hospital in the Free State. This raises another possibility, namely that the high prevalence of stunting in the South African setting could play a role in the finding that knee height-based equations deliver better predictions than arm-based equations.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…On the other hand, published arm-based equations did not accurately predict height in a sample of 900 younger adults in KwaZulu-Natal, and the study concluded that sex-and racespecific equations are needed. 15 This concurs with the findings of van den Berg et al 1 that the ulna-based MUST equations overestimated height and predicted height that differed statistically significantly from stadiometer height in adult (20-60 years old) patients in a public hospital in the Free State. This raises another possibility, namely that the high prevalence of stunting in the South African setting could play a role in the finding that knee height-based equations deliver better predictions than arm-based equations.…”
Section: Discussionsupporting
confidence: 86%
“…Amongst many other clinical applications, accurate height measurements are required to calculate body mass index (BMI) and ideal bodyweight (IBW), which, in turn, are used in nutritional screening and the calculation of nutritional requirements of patients. 1,2 International consensus advises that all patients should be screened for nutritional risk on admission, 3 and throughout the hospital stay 3 so that appropriate dietary intervention based on these screenings can be employed to improve and maintain proper nutritional status. [3][4][5] Whereas some patients are admitted with poor nutritional status, others develop disease-related malnutrition during hospitalisation.…”
Section: Introductionmentioning
confidence: 99%
“…Contrary to published reports that primates in captivity or sanctuaries are often larger than wild populations due to the increased caloric value of human-provisioned diets (i.e., as found by Turner et al, 2016b, on St. Kitts), vervets of both sexes from the well-sampled Riverside Wildlife Rehabilitation Centre in Limpopo do not appear to be significantly heavier than wild-trapped populations in South Africa, although they were considerably smaller in body length at almost every age while also appearing to have comparatively long thigh and leg lengths relative to other populations sampled in South Africa. This differently proportioned body may reflect the poor nutrition or early life trauma that are characteristic of pets or rescued wildlife (e.g., Jones-Engel et al., 2001), as stunting based on poor nutrition and systemic disease has been noted to affect body length disproportionately to limb length, resulting in relatively longer limbs (e.g., Krishna et al, 1996; van den Berg et al, 2016). The divergent growth patterns in body length of vervets sampled in Mpumalanga may be due to their being largely sampled at or near tourist resorts at Swadini, Londolozi, and Blyde River Canyon.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have agreed that there is a high degree of inaccuracy when measuring with a tape measure. 3,6,13 However, tape measures have been used in several studies that were conducted in the adult population and demonstrated correlations between ulna length and height. 16,17,19,22 Furthermore, tape measures are cheaper and more accessible than anthropometric calipers.…”
Section: Discussionmentioning
confidence: 99%
“…Standing height is usually considered the gold standard measurement of height, 5 which requires the individual to stand erect and unassisted when being measured with a calibrated stadiometer. 6 However, measurement can be difficult for those who are unable to stand upright, those who are critically ill, or those who have paralysis, limb and/or vertebral column deformity or neuromuscular weakness. 3 Furthermore, using a stadiometer in field studies may be difficult as a result of portability and accessibility issues.…”
Section: Introductionmentioning
confidence: 99%